1996
DOI: 10.1136/bjo.80.4.297
|View full text |Cite
|
Sign up to set email alerts
|

Objective detection of hemifield and quadrantic field defects by visual evoked cortical potentials.

Abstract: Aims/Background-An objective method for detecting hemifield and quadrantic visual field defects has been developed using steady state visual evoked cortical potentials (VECPs), an adaptive noise cancelier (ANC), and Hotelling's t2 statistic. The purpose ofthis study was to determine the sensitivity and specificity of the technique. Methods-Nine subjects (mean age 44 years) were investigated with field loss due to a variety of causes including both anterior and posterior visual pathway lesions. Dynamic perimetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…This finding may be due to the lower signal-to-noise ratio when the aggregate cone stimulation was minimal with those very peripheral-only stimuli. The notion of high repeatability, in conjunction with the aforementioned finding of relatively good linearity, support the concept of using the VEP as an objective indicator of visual-field dysfunction, as has been suggested and tested to some degree in earlier studies [9,[23][24][25][26][27][28][29]. 14 Relationship between total cumulative increase in cone number (X 1,000/mm 2 ) and mean VEP amplitude (microvolts) with increase in stimulus diameter Fig.…”
Section: Visual-field Test Condition Mean Amplitude (Microvolts)mentioning
confidence: 72%
See 1 more Smart Citation
“…This finding may be due to the lower signal-to-noise ratio when the aggregate cone stimulation was minimal with those very peripheral-only stimuli. The notion of high repeatability, in conjunction with the aforementioned finding of relatively good linearity, support the concept of using the VEP as an objective indicator of visual-field dysfunction, as has been suggested and tested to some degree in earlier studies [9,[23][24][25][26][27][28][29]. 14 Relationship between total cumulative increase in cone number (X 1,000/mm 2 ) and mean VEP amplitude (microvolts) with increase in stimulus diameter Fig.…”
Section: Visual-field Test Condition Mean Amplitude (Microvolts)mentioning
confidence: 72%
“…Furthermore, it provides global real-time information as to the patient's performance (i.e., assessing VEP amplitude and latency as the averaged responses dynamically summate over time) for the specific stimulus pattern. Moreover, the objective VEP information can be used to correlate with, and corroborate, the conventional subjective psychophysical results of a clinical visualfield assessment [9].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the present data showed that maximal SNRs can be found in any one of the six channels. For improvement of the SNR, in future studies with the steady-state technique, the benefit of additional (e.g., forehead) electrodes [28,35] [12] should be investigated. Using such electrode setups, the combined evaluation of orthogonal signals (Euclidian sum) might reveal larger SNRs than any single channel [29].…”
Section: Discussionmentioning
confidence: 99%
“…A strong correlation between O z , and the average of O 1 and O 2 is a good indication of the overall associations between neural and vascular activation. 69,70 In summary, specific changes were observed across both VEPs and hemoglobin concentration levels in response to onset and static stimulation. In agreement with previous studies, we suggested that the N1-P2 complex could be a marker of stereopsis in V1.…”
Section: Correlation Between Veps and Hbo Concentrationmentioning
confidence: 99%